Indonesia ANALISIS PENGARUH BIAYA ADVERTISING, BIAYA PERSONAL SELLING, DAN BIAYA SALES PROMOTION TERHADAP LABA BERSIH PADA PT. MITRA JAYA NUSA PERSADA: Indonesia - Luthfia Ayu Karina; Puji Rahayu; Nazaruddin (P3M Politeknik Negeri Banjarmasin, 2021)
ABSTRACT This study was conducted to analyze the effect of both simultaneously and partially between advertising costs, personal selling costs, and sales promotion costs on the net profit of PT. Mitra Jaya Nusa Persada for the period January 2018 to December 2019. The method used in this study is a quantitative method and the analysis used is statistical descriptive table test, classical assumption test and hypothesis testing using multiple linear regression test, coefficient of determination test, and partial t test, and the simultaneous f-test using the SPSS version 25 computer program. Based on the test results, simultaneously advertising costs, personal selling costs, and sales promotion costs only have an effect on net profit of 9.4%. While the remaining 91.6% is influenced by other factors. While partially shows that advertising costs, personal selling costs, and sales promotion costs have an influence but are not significant and sales promotion costs are the variables that have the most dominant influence on the net profit of PT. Mitra Jaya Nusa Persada. Keywords: Cost, Advertising, Personal Selling, Sales Promotion, Net Profit